Pengaruh Kompetensi dan Motivasi Kerja Terhadap Pelayanan Prima Karyawan di PT BPR Syariah Muamalah Cilegon - Haris Wibowo; Efi Syarifudin; Oom Mukaromah (TSARWAH, 2022)
Working or seeking sustenance in sharia economics needs to pay attention to contract agreements and the prohibition of usury, so there needs to be consideration in choosing an institution to carry out Islamic economic activities. PT BPR Syariah Muamalah Cilegon is a financial institution with a sharia economic concept. The formulation of the problem and objectives in this study are related to the effect of work competence on employee excellent service, the effect of work motivation on employee excellent service and the influence of competence and work motivation together on excellent service for employees of PT BPR Syariah Muamalah. The method in this study uses a quantitative method with a causal relationship and an explanatory survey is carried out through a deductive approach, which aims to explain the position of the variables studied and the influence between one variable and another. Sources of data used are primary data and secondary data. The results of this study indicate that there is a significant influence between Work Competence and Work Motivation on Excellent Service Employees either partially or simultaneously, this is because the significant value of each independent variable on the dependent variable is < 0,05 so H0 is rejected and H1 is accepted. Keywords: work competence, work motivation, excellent service